Motivasi Karyawan RSI PKU Muhammadiyah Palangka Raya untuk Mengaji Al-Qur’an - Anggi Nor Fajaria; Arini Safitri (Syams, 2020)
This paper aims to obtain an overview of the implementation of group guidance in motivating RSI PKU Muhammadiyah Palangka Raya employees to read the Al-Qur'an, and exploring the effectiveness of group guidance in motivating employees of RSI PKU Muhammadiyah Palangka Raya to read the Al-Qur’an. This type of research is a pre-experimental study with one group pre-post test design. The instruments used consisted of a motivation questionnaire to read the Qur’an, the implementation of the treatment, observation and interviews. This article shows that: 1) The implementation of group guidance in motivating employees of RSI PKU Muhammadiyah Palangka Raya to read the Al-Qur’an during four meetings, namely the first meeting data collection, the second meeting group guidance services with group discussion techniques, the third meeting of information services with group discussion techniques, four evaluation meetings and follow-up group guidance. Members of 7 employees who are willing to participate in group guidance activities. 2) The effectiveness of group guidance in motivating the employees of RSI PKU Muhammadiyah Palangka Raya to read the Al-Qur'an is seen as effective, seen from the increase in the pre-test average score of 56.86% and the post-test increase of 78.57% with an average score There was a significant increase in results between before and after treatment.